1994
DOI: 10.1007/bf02052599
|View full text |Cite
|
Sign up to set email alerts
|

Tumor angiogenesis and rectal carcinoma

Abstract: Our results suggest that the growth of rectal cancer is dependent on the ingrowth of new blood vessels, and that increased vascularity promotes dissemination and adversely affects survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
57
1
2

Year Published

1996
1996
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(63 citation statements)
references
References 8 publications
3
57
1
2
Order By: Relevance
“…with deeper tissue invasion. This finding is comparable to previous reports which claim that the tumor spreading activity is fueled by angiogenesis (20,23,26) . CHOI et al (5) found a non-significant difference between high microvessel counts and deeper tumor invasion.…”
Section: Microvessel Count and Patient Survivalsupporting
confidence: 91%
“…with deeper tissue invasion. This finding is comparable to previous reports which claim that the tumor spreading activity is fueled by angiogenesis (20,23,26) . CHOI et al (5) found a non-significant difference between high microvessel counts and deeper tumor invasion.…”
Section: Microvessel Count and Patient Survivalsupporting
confidence: 91%
“…Microvessel density has been shown to be an independent parameter of the severity of tumour disease and a predictor of prognosis of breast cancer patients in most but not all studies addressing this issue (Weidner et al, 1991(Weidner et al, , 1992Bosari et al, 1992;Horak et al, 1992;Toi et al, 1993, Axelsson et al, 1995. A similar correlation has also been demonstrated with other human malignancies, including head and neck squamous cell carcinoma (Gasparini et al, 1993), lung adenocarcinoma (Yamazaki et al, 1994), rectal carcinoma (Saclarides et al, 1994), testicular germ cell tumours (Olivarez et al, 1994), prostate cancer , tumours of the oral cavity (Williams et al, 1994) and gastric carcinoma (Maeda et al, 1995 rie receptor in breast cancer P Salven et al higher when staining was performed using the clone 7E8 antibody (Table I). No specific staining was observed when the sections were incubated with antigen-blocked antibody instead of the primary antibodies, or with the peroxidaseconjugated secondary antibody only.…”
mentioning
confidence: 71%
“…High MVD has been associated with a poorer outcome in some studies of CRC (Saclarides et al, 1994;Tanigawa et al, 1997). Our results concur with this, with high MVD primary cancers and liver metastases having a reduced disease-free survival.…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer (Uzzan et al, 2004), non-small cell lung carcinoma (Ushijima et al, 2001) and melanoma (Ribatti et al, 2003), a high MVD is associated with poor outcome. In CRC, a high MVD has been shown to predict disease recurrence and survival in some studies (Saclarides et al, 1994;Tanigawa et al, 1997), whereas other studies have shown an association between high MVD and improved survival (Prall et al, 2003) or have concluded that MVD failed to provide additional prognostic information (Cianchi et al, 2002).…”
mentioning
confidence: 99%